The Hijab and Muslim women's employment in the United States. (June 2019) - Abdelhadi, Eman
Highlights: Muslim women who wear the hijab in the United States are far less likely to be employed than nonMuslim women. Muslim women who do not wear the hijab are not significantly less likely to be employed than nonMuslim women. About a third of the effect among Muslim women is explained by sociodemographic differences. Abstract: A substantial body of empirical evidence suggests that employment benefits women, yet Muslim women consistently work for pay less than other women. This article extends the question of religion differences in employment to the United States, where—due to a paucity of data—we know little about Muslim women and their economic outcomes. The analysis uses the only known probability-sample surveys of Muslims in the U.S., conducted by the Pew Research Center in 2007 and 2011. These are pooled with the 2010 General Social Survey to provide the first comparative analysis of employment among Muslim and nonMuslim women using probability samples. I assess whether Muslim women in the United States work for pay less than their nonMuslim counterparts, and whether socio-demographic characteristics explain these differences. I find that the likelihood of employment for Muslim women who do not wear the hijab does not differ significantly from the likelihood of employment for nonMuslim women. However, women who wear the hijab have a much lower likelihood of employment than nonMuslim women or non-veiling Muslim women. The remainder of the analysis focuses on intra-Muslim differences, exploring what factors mediate "the hijab effect" on women's employment. I find that demographic, human capital, and household composition variables mediate about one third of the effect, while the rest remains unexplained.